KORELASI ANTARA JENIS KELAMIN DENGAN BOBOT KARKAS SAPI SIMPO DI RUMAH POTONG HEWAN KOTA BLITAR - Resti Yuliana Rahmawati; Yuhanin Zamrodah; joko prasetyo (AVES: Jurnal Ilmu Peternakan, 2024)
This study aims to determine whether there is a relationship between sex and carcass weight of SIMPO cattle at the Slaughterhouse, Sukorejo District, Blitar City. This research was conducted for 2 weeks in June 2023 and data collection was carried out at the Sukorejo District Slaughterhouse, Blitar City. The research method used was a field study at RPH Blitar City. The materials used in this study were 30 male and female SIMPO cattle and 30 carcasses. The obtained data was processed by using Microsoft Excel to find out the results of the correlation between sex and carcass weight of SIMPO cattle. The results showed that the correlation between male and female with moderate carcass weight was 0.46. The average carcass weight for bulls is 212.26 kg, while for cattle it is 168.45 kg. These results indicate that male and female sexes have a correlation or relationship with the carcass weight produced.